The adaptation process of a safety planning intervention to promote connectedness and reduce distress in Diné adolescents and adults during the COVID-19 pandemic - Allison-Burbank, Joshuaa Dominic; Begaye, Vanessa; Dedman-Cisco, Kyann; Jim, Lisa; Archuleta, Shannon; Begay, Renae; Howe, Lacey; Haroz, Emily E. (Frontiers in Public Health, 2025)
Introduction Indigenous connectedness is an impetus for health, well-being, self-confidence, cultural preservation, and communal thriving. When this connectedness is disrupted, the beliefs, values, and ways of life that weave Indigenous communities together is threatened. In the Spring of 2020, the COVID-19 virus crept into Tribal Nations across the United States and exacerbated significant health-related and educational inequities. The first case of COVID-19, or Dikos Ntsaaígíí-19 in the Diné (Navajo) language, arrived in the Southwest in March 2020. The virus quickly spread amongst Diné communities and contributed to immediate school closures. These closures created significant disruption to connectedness on the Navajo Nation. Methods As part of the Community Based Participatory Research process, our team worked with a Community Advisory Board (CAB) to facilitate a longitudinal cohort study titled “Project SafeSchools” and, most critically, to culturally adapt mental health interventions to be implemented as a part of this study. This paper describes the process our team used to select, adapt, and test Safety Planning and Caring Contacts interventions to reduce elevated rates of depression, anxiety, and suicidal ideation amongst Diné adolescents and adults. CBPR was the primary approach used to engage with Navajo Nation communities and the adaptation process was guided by a scoping study of frameworks for adapting public health evidence-based interventions (EBI) and was guided by the cultural adaptation process. Our team met virtually several times in 2021 and 2022 as the parent launched and as the pilot randomized clinical trial called “+Connection is Medicine” started. When Safety Planning and Caring Contacts messaging was selected, the study team, which consisted primarily of Navajo research personnel led by a Navajo community-based principal investigator (PI) and allied PIs with extensive experience in implementation science, infectious disease prevention, and CBPR, were adapted and presented to CAB members. This CAB also included a youth advisory council who participated in the field testing and further adaptation process. Results The use of the CAB allowed for a collaborative workgroup effort to examine the feasibility and acceptability of using safety planning to help reduce suicide risk factors with Navajo adolescents and adults. Most importantly, this CAB collaborative with researchers to further tailor safety plan intervention materials to align with Navajo values related to connectedness to relatives, community, mental health resources, and the land. In addition, the caring contacts messaging was aligned with safety plans to provide culturally sensitive messages that would be shared with randomized participants. Discussion Mental health stigma is highly common in reservation-based communities. In Indigenous communities, mental illness has association with not living well or not living culturally aligned further complicates the likelihood of at-risk community members contacting resources available in their communities. By using an Indigenous approach that restores connectedness, and reminds participants of their belonging, +CiM researchers were able to develop enhanced versions of safety plans to use in their pilot randomized controlled trial.